Education in the Midst of Indonesia’s Development Agenda - Rizqyansyah Fitramadhana (Faculty of Social Science, Universitas Negeri Malang, 2023)
President Jokowi made a shocking decision in his second term by pointing to Nadiem Makarim as Minister of Education, Culture, Research, and Technology. Not long after his appointment, Nadiem Makarim released Merdeka Belajar and Peta Jalan Pendidikan Indonesia 2020-2035, which is significant to Indonesia’s education context. Those two stipulations alone indicate exponential change within education governance in Indonesia. Various notable scholars later argue that Nadiem Makarim’s policy is intriguing and essential, emphasizing their support for Merdeka Belajar and Peta Jalan Pendidikan Indonesia 2020-2035. A glance at scientific articles published right after enacting these two policies shows that many, if not most, researchers agree thoroughly with Nadiem Makarim. In contrast with the previous undertaking, this study uses critical explanations to expose and unearth the interest lurking beneath the so-called neutral policy agenda. To support the aim of this research, a critical policy study paradigm will be used along with the critical discourse analysis of Norman Fairclough. There are two significant findings from an in-depth search of the study of the text production process, text analysis, and interpretation of discourse and social practices of education policy during the Jokowi era. First, in the eye of Jokowi’s administration, education is part of the development business. Education, in short, is seen as a proper tool (a) to adapt to the current condition of the knowledge-based economy and to cultivate human resources and (b) to build a young generation (Profil Pelajar Pancasila) who can thrive in the changing world without losing its grip on Pancasila as the main symbol of Indonesia. Second, Jokowi’s education discourses and social practices are spurred by the urgent need to reskill, upskill, and enhance the employability of both workers and future workers. These two propositions are corroborated by the production of texts that are thick with institutional interests in the form of increasing human capital for Indonesia's Vision 2045, text analysis that shows the dominance of representation of human resource development interests in various policy documents in Indonesia, and interpretation of discourse that hints at the existence of link and match hegemony in human resource development projects as well as efforts to align cognitive and ethical aspects through the P5 program